Addressing the silver tsunami in the accounting industry. Issue 1 (5th February 2021) - Dorr, Brian M.; Feuerhelm, Shannon L.
Abstract : Purpose: As Baby Boomers continue to retire, organizations should have plans in place that successfully execute this transition. Some industries, such as accounting, are unique in that there is specialized knowledge required by employees, including education and work experience. This study examines what accounting organizations are doing to manage this transition. The research question posed is as follows: How are organizations in the accounting industry addressing anticipated retirements?. Design/methodology/approach: This is a qualitative study that is interpretive. In order to answer the research question, six managers who are involved in the hiring process at accounting organizations of varying sizes were interviewed. Semi-structured interviews were conducted and coded using the software program, Dedoose, in order to develop themes that addressed the research question. Findings: By conducting semi-structured interviews that focused on efforts related to this issue, it was found that accounting organizations are focusing on three aspects related to the research question: Accounting firms are focusing on (1) culture, (2) knowledge and (3) transition as they lead their organizations through this time. Practical implications: This research project provides insight into how some accounting organizations are managing issues related to increasing retirements. By knowing how other organizations are handling these issues, accounting organizations can use this knowledge to prepare, themselves, for anticipated retirements. This knowledge is also valuable in other fields that provide professional services (e.g., medical and legal). Originality/value: This topic has not been fully explored in the accounting industry. The findings of this study are useful to accounting firms, world-wide, as well as to organizations in other professional services fields, world-wide. This research could be further explored in other professional services organizations, such as the health and legal fields.